MENUMBUHKAN KARAKTER SISWA MELALUI OPTIMALISASI PERAN GURU PAK - Glesy Claudia Sidabutar; Debora Lidya Padang; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
This research aims to examine the roles and duties of Christian religious education teachers. Character education is an important aspect of education, especially in forming a young generation with morals and noble character. Christian Religious Education (PAK) teachers have an important role in shaping student character based on Christian values. Religious education has a crucial role in forming student character, especially in the context of Christian education. This research aims to investigate the role of Christian religious education teachers in shaping student character. Qualitative research methods were used to gain an in-depth understanding of the experiences and perspectives of teachers and students. Data was collected through in-depth interviews and observations in several secondary schools that have Christian religious education programs. The findings show that Christian religious education teachers play an important role in guiding students to develop character in accordance with Christian values such as love, patience, honesty and responsibility. They use a variety of strategies, including Bible stories, group discussions, and practical examples, to inspire and guide students in integrating these values into their daily lives. Apart from that, cooperation between teachers, parents and the church is also considered crucial in supporting the formation of student character. The implications of this research highlight the importance of training and mentoring for Christian religious education teachers so that they can play their role effectively in shaping student character. Further research is also recommended to further explore the dynamics of the relationship between Christian religious education and student character formation in different contexts.